Numerical Study of the Use of Shear-Thinning Nanofluids in a Microchannel Heat Sink with Different Pin Densities and Including Vortex Generator - Castillo-Del Barrio, E; Gonzalez-Andres, A (Elsevier Ltd, 2024)
This article numerically investigates the thermal and hydraulic performance of shear-thinning nanofluids when used as heat-conducting fluids in a microchannel heat sink device. Five geometries are evaluated: four with different pin densities and one with vortex generators. Six Reynolds numbers are studied, ranging between 200 and 1200. Numerical experiments show a comparison of using a water/ethylene-glycol mixture with and without alumina nanoparticles and multiwalled carbon nanotubes. Two different concentrations of nanoparticles were evaluated, both given shear-thinning nanofluid behavior. The viscous properties of the fluids are fitted from previously reported experimental data. The other thermophysical properties are modeled using single-phase expressions adjusted to consider hybrid nanofluids. Numerical results show that the heat transfer rates and pressure drop increase when the pin density increases, resulting in thermal blocking in the case of higher pin density. These key findings are a result of the increase in the heat transfer of shear-thinning nanofluids and the reduction of the pressure drop when compared with Newtonian fluids. Apparent viscosity contours are used to understand the thermal and hydraulic performance. Between the two nanofluids studied, the one with the lowest power-law index was the best in terms of heat extraction and pressure drop, indicating that fluids with thinning rheology may be recommended for heat transport in microchannel heat sink devices. © 2024 The Authors